Temples of the Grail : the search for the world's greatest relic - Matthews, John, 1948-; Knight, Gareth (Llewellyn Publications, 2019)
Explore the transformative power of the Grail and discover extraordinary revelations from nearly forgotten Grail texts. Temple of the Grail offers the first English translations of the thirteenth-century Sone de Nansay and the Later Titurel by Albrecht, together with insights from the Letter of Prester John. These texts, along with brilliant commentary by foremost Grail scholars John Matthews and Gareth Knight, provide tantalizing clues into the modern understanding of the Grail quest, shedding important new light on the mysteries of the Grail temple itself, its relationship to the sacred understanding of architecture and symbolism, and its rediscovery in the heart of the Middle East. In addition, Temple of the Grail explores the lineage of the mystical Swan Knights, said to be guardians of the Grail descended from Sone himself. Filled with fascinating perspectives on one of the greatest mysteries of all time, this book is a must-have for Grail aficionados. The interpretations of the Grail temple and the effects of standing before the Grail live at the heart of the mystery. The profound ideas explored in Temple of the Grail open new pathways of engagement with this essential part of our continued spiritual evolution.